The Effects of Trauma History and Prenatal Affective Symptoms on Obstetric Outcomes. Issue 3 (8th June 2016) - Blackmore, Emma Robertson; Putnam, Frank W.; Pressman, Eva K.; Rubinow, David R.; Putnam, Karen T.; Matthieu, Monica M.; Gilchrist, Michelle A.; Jones, Ian; O'Connor, Thomas G.
Abstract: Prenatal maternal mood may inform the adverse obstetric outcomes seen in disadvantaged populations. The contribution of having a trauma history is not well studied. We examined the impact of trauma exposure and mood symptoms on obstetric outcomes in 358 women. Women with antecedent trauma were more likely to have a history of depression, odds ratio = 2.83, 95% confidence interval [1.81, 4.42], were younger at their first pregnancy, 18.86 years versus 20.10 years, and had a higher number of previous pregnancies, 2.01 versus 1.54, compared to those with no trauma exposure. Women with prenatal anxiety had significantly smaller babies than nonanxious women, 3, 313.17 g, ( SD = 441.58) versus 3, 429.27 g, ( SD = 437.82) Trauma history magnified the effects of maternal prenatal mood on birthweight; the moderating effect was limited to those who first experienced a trauma under 18 years of age. Childhood trauma exposure increased vulnerability for low birthweight delivery associated with prenatal mood disturbance. Screening pregnant women for trauma history and current mood symptoms is indicated.